Protecting democracy from dissent - Monaghan, Shannon, author.
1 online resource
Keywords: "In the aftermath of the First World War, the victorious powers argued that democracy would bring peace to Europe because this was the only effective way for legitimate states, with governments based on the consent of the governed, to be organized. What the victorious statesmen failed to foresee was how much conflict this postwar settlement would provoke, since it was far from clear exactly which people should qualify for the privilege of self-governance. While the victors sought to craft a more legalistic form of population engineering than the often violent and ad hoc versions employed further east, the result nevertheless remained at odds with the ethical foundations of liberal democracy"--Provided by publisher.